Prediction on inflation of education in Malaysia - Mohd Akhir, Ashwaq; Khalid, Kamil; Rusiman, Mohd Saifullah (Enhanced Knowledge in Sciences and Technology, 2024)
The critical issue of price inflation in the education sector in Malaysia, aiming to develop a robust forecasting model to predict future price trends. As the cost of education continues to rise, understanding and predicting inflationary patterns becomes essential for policy-makers, educational institutions, and stakeholders alike. This project employs a data-driven approach, leveraging historical pricing data, economic indicators, and machine learning techniques to model and forecast the inflation rates specifically tailored to the Malaysian education sector.The anticipated outcomes of this research include a predictive model capable of providing timely and accurate forecasts for education price inflation in Malaysia. This tool can serve as a valuable resource for educational policymakers, institutions, and individuals planning for future education expenses. By gaining insights into future price trends, stakeholders can make informed decisions, implement proactive financial strategies, and contribute to the ongoing discourse on addressing the affordability and accessibility of education.